Enhancement of iodinin solubility by encapsulation into cyclodextrin nanoparticles. (1st January 2018) - Prandina, Anthony; Herfindal, Lars; Radix, Sylvie; Rongved, Pål; Døskeland, Stein O.; Le Borgne, Marc; Perret, Florent
Abstract: Phenazine is known to regroup planar nitrogen-containing heterocyclic compounds. It was used here to enhance the bioavailability of the biologically important compound iodinin, which is near insoluble in aqueous solutions. Its water solubility has led to the development of new formulations using diverse amphiphilic α-cyclodextrins (CDs). With the per-[6-desoxy-6-(3-perfluorohexylpropanethio)-2, 3-di- O -methyl]-α-CD, we succeeded to get iodinin-loaded nanoformulations with good parameters such as a size of 97.9 nm, 62% encapsulation efficiency and efficient control release. The study presents an interesting alternative to optimizing the water solubility of iodinin by chemical modifications of iodinin.